Don't waste the crisis: critical perspectives for a new economic model (Geneva, 2010)
"This collection of short articles examines the causes and consequences of the global financial crisis, with a focus on labour. The articles suggest ways to strengthen labour’s capacity to influence policy debate, offering inspiration to those who feel that national and international policies must change and who are convinced that the labour movement has much to contribute after years of declining influence."